Natural History of Postoperative Adding-On in Adolescent Idiopathic Scoliosis: What Are the Risk Factors for Progressive Adding-On?. (29th March 2018) - Qin, Xiaodong; Xia, Chao; Xu, Leilei; Sheng, Fei; Yan, Huang; Qiu, Yong; Zhu, Zezhang
Abstract : Purpose. To investigate the natural history of distal adding-on in adolescent idiopathic scoliosis (AIS) and to identify risk factors for its progression. Methods. Sixty-one AIS patients with distal adding-on occurrence were included. We further classify distal adding-on into progressive and nonprogressive group according to its natural evolution. The first radiograph indicating initiation of adding-on (primary adding-on) and the last follow-up radiograph were compared in terms of the deviation of the first vertebra below instrumentation from the CSVL and the angulation of the first disc below instrumentation. Compared to primary adding-on, progressive adding-on was defined as a further increase of deviation > 5 mm or a further increase of angulation > 5°. Risk factors associated with the progression of adding-on were analyzed. Results. Among 61 patients diagnosed with distal adding-on, 24 (39.3%) were progressive and 37 (60.7%) were nonprogressive. Lower Risser grade, open triradiate cartilage, and lowest instrumented vertebra (LIV) proximal to Substantially Stable Vertebra (SSV) were found to be significantly associated with the progressive adding-on. Besides, the distal adding-on was more likely to progress for patients with higher left shoulders than right ones after surgery. Conclusions. The risk factors for the progression of adding-on included skeletal immaturity, LIV proximal to SSV, and higher left shoulders after surgery.